2016
DOI: 10.2147/ott.s96861
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of miR-20a expression suppresses cell proliferation, migration, and invasion in HepG2 cells

Abstract: ObjectiveTo study microRNA (miR)-20a expression in hepatocellular carcinoma (HCC) and its effects on the proliferation, migration, and invasion of HepG2.MethodsThe real-time polymerase chain reaction was used to detect the expression of miR-20a in HCC tissue and normal tissue, as well as in HCC cell lines and normal liver cells. miR-20a mimic and miR negative control (NC) were transfected into HepG2 cells. MTT (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide) assay was used to detect cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…However, some patients still have lower Taxol sensitivity because of drug resistance, which leads to poor prognosis of patients (8). Recently, altered levels of autophagy and miRNAs were attractive candidates for study as regulators of chemosensitivity in breast cancer (11,16,26). In the present study, we found that miR-129-5p increased the Taxol-induced apoptosis while inhibiting autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some patients still have lower Taxol sensitivity because of drug resistance, which leads to poor prognosis of patients (8). Recently, altered levels of autophagy and miRNAs were attractive candidates for study as regulators of chemosensitivity in breast cancer (11,16,26). In the present study, we found that miR-129-5p increased the Taxol-induced apoptosis while inhibiting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Micro RNAs (miRNAs) are a class of short, endogenous, non-coding RNAs (∼20–24 nucleotides) that regulate the expression of a diversity of genes (10). They have been identified to be involved in a variety of biological processes (11 13). Recently, an increasing number of studies have reported that dysregulation of miRNAs might be related to drug resistance (14 16).…”
Section: Introductionmentioning
confidence: 99%
“…miR-20a: the dysregulation of miR-20a expression is involved in the development of a variety of cancers [ 113 ]. In PH, miR-20a targets PKG1, promotes the activation of Elk-1, and competes for the binding sites of MYOCD and SRF, eventually leading to the dissociation of the MYOCD-SRF complex and termination of the SM-specific gene expression programme.…”
Section: Mirnas Modulate Pasmcs Phenotypic Switchingmentioning
confidence: 99%